The Development of an Interactive Learning Website Based on Google Sites on Photosynthesis Material - Magfirah Rasyid; Yusmar Yusuf; Ningsi Saibi; WD. Syarni Tala; Aswal Salewangeng (JURNAL BIOEDUKASI, 2025)
Learning media can help improve understanding and facilitate the interpretation of learning materials. They also play a role in generating enthusiasm and interest in learning among students. The purpose of this research is to develop a learning media website based on Google Sites and to test the validity and practicality of the media that has been developed. The developed website will be used in plant physiology courses on photosynthesis material. The research and development follows the 1974 Thiagarajan model of 4D (Define, Design, Develop and Disseminate). The results showed that the interactive learning website based on Google sites was highly valid for learning, with percentages of 96% from material experts, 96% from media experts and 97% from educational practitioners. The level of practicality of the websites was found to be 91%, as determined by student responses. This means that the learning website development is very valid and feasible to use.